A single cystatin C determination before coronary angiography can predict short and long-term adverse events. (1st February 2020) - Budano, Carlo; Andreis, Alessandro; De Filippo, Ovidio; Bissolino, Arianna; Lanfranco, Giacomo; Usmiani, Tullio; Gai, Massimo; Levis, Mario; Bergamasco, Laura; Marra, Sebastiano; Rinaldi, Mauro; Ferrari, Gaetano Maria De
Abstract: Background: Cystatin C (CyC) role in the detection of contrast induced acute kidney injury (CIAKI) is controversial. This study assessed whether a single CyC determination before coronary angiography (CA)could predict CIAKI and long-term adverse events. methods: CyC was assessed before CA in 713 consecutive patients. CIAKI was the primary endpoint, defined as ≥0.3 mg/dl creatinine (sCR) increase at 48 h or ≥50% in 7-days. All-cause death, cardiovascular (CV)death and MACE (acute coronary syndrome, acute pulmonary edema, CV death) were secondary endpoints. Re-hospitalization, in-hospital death and worsening renal function were tertiary endpoints. Results: CIAKI occurred in 47 (6.7%) patients. ROC analysis showed a good accuracy of CyC in the prediction of CIAKI (AUC 0.82, p < 0.01), compared with baseline sCR and sCR-eGFR (AUC 0.70 and 0.75 respectively, both p < 0.01). CyC was associated with 10-year CV-death, all-cause death and MACEs (AUC 0.76, 0.74 and 0.64 respectively, all p < 0.01). A CyC cut-off value of 1.4 mg/L was not only accurate in predicting or ruling-out CIAKI following CA (97% negative predictive value, 84% specificity), but also useful as a prognostic marker for 10-year adverse events (50% vs.16% all cause mortality, 29% vs.3% CV death, 39% vs.13% MACE, all p < 0.01), re-hospitalizations (54% vs.35%, p < 0.01) and worsening renal function (34% vs.19%, p < 0.01). The strongest and independent risk factor for 10-year CV death was baseline CyC>1.4 mg/L (HR 17.3, 95% CI 1.94–155.1). Conclusions: A baseline determination of CyC before CA can accurately rule out CIAKI and predict adverse events in the long term. CIAKI can be ruled out before CA in 97% patients with a CyC value < 1.4 mg/L. Highlights: CyC can predict or rule-out CIAKI before coronary angiography. CyC is more accurate than creatinine/eGFR in CIAKI prediction. CyC≥1.4 mg/L before coronary angiography predicts long-term events.